Endophyte enhanced banana tissue culture: technology transfer through publicprivate partnerships in Kenya and Uganda - Dubois, T.; Coyne, Danny L.; Kahangi, E.; Turoop, L.; Nsubuga, E. (2006)
The lack of clean planting material is a major constraint for banana production in East and Central Africa. When establishing new fields, tissue culture plantlets will reduce damage by banana pests and diseases. Pest infestation or reinfestation, however, remains a vital concern. Fungal endophytes, when inoculated into banana tissue culture plants, extend the benefits of clean planting material. Endophyte-enhanced tissue culture technology is being developed at the International Institute of Tropical Agriculture (IITA). Tissue culture production facilities in Uganda are in their infancy, while in Kenya the situation is more developed. Public-private partnerships between IITA and Agro-Genetic Technologies Ltd (Uganda), and Jomo Kenyatta University of Agriculture and Technology (Kenya) have recently enabled IITA’s project to make great progress towards bridging upstream research and downstream technology transfer. Additionally, unexpected synergisms have emerged through mutual exchange of information and experience. Based on IITA’s highly positive experience, such public-private partnerships should be introduced as early as possible in the developmental stages of activities to maximize the benefits to research for development.